Rapid diagnosis of Argentine hemorrhagic fever by reverse transcriptase PCR-based assay. - Lozano, M E (1995)
Argentine hemorrhagic fever (AHF) is an endemo-epidemic disease caused by Junín virus. This report demonstrates that a reverse transcriptase (RT) PCR-based assay developed in our laboratory to detect Junín virus in whole blood samples is sensitive and specific. The experiments were conducted in a double-blinded manner using 94 clinical samples collected in the area in which AHF is endemic. The RT-PCR-based assay was compared with traditional methodologies, including enzyme-linked immunosorbent assay, plaque neutralization tests, and occasionally viral isolation. The calculated parameters for RT-PCR diagnosis, with seroconversion as the "gold standard," were 98% sensitivity and 76% specificity. It is noteworthy that 94% of the patients with putative false-positive results (RT-PCR positive and no seroconversion detected) exhibited febrile syndromes of undefined etiology. These results could be interpreted to mean that most of those patients with febrile syndromes were actually infected with Junín virus but did not develop a detectable immune response. Furthermore, 8 laboratory-fabricated samples and 25 blood samples of patients outside the area in which AHF is endemic tested in a similar way were disclosed correctly (100% match). The RT-PCR assay is the only laboratory test available currently for the early and rapid diagnosis of AHF. It is sensitive enough to detect the low viremia found during the period in which immune plasma therapy can be used effectively, reducing mortality rates from 30% to less than 1%.